Features Of Implementation Of Criteria-Based Assessment Technology In A Modern Educational Process (Eurasian Journal of Learning and Academic Teaching, 2024)
The article gives a summary of the utilization of criteria-based assessment technology adapted to the conditions of Uzbek education in the framework of the implementation of the priority regional project "Creation of an international Bachelor`s system in Kashkadarya region of the Republic of Uzbekistan", taking into account the requirements of the state educational standard of the republic. The authors reveal the main goals, objectives and principles of assessment, gives an example